2001
DOI: 10.1056/nejmoa012175
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Use of a Left Ventricular Assist Device for End-Stage Heart Failure

Abstract: The use of a left ventricular assist device in patients with advanced heart failure resulted in a clinically meaningful survival benefit and an improved quality of life. A left ventricular assist device is an acceptable alternative therapy in selected patients who are not candidates for cardiac transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
1,921
1
52

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 3,703 publications
(2,034 citation statements)
references
References 25 publications
21
1,921
1
52
Order By: Relevance
“…Several other studies have concluded that LVAD support is an excellent tool as bridge to transplant [9,10]. As shown by the REMATCH study [3], the role of LVAD support is not only limited as bridge to HTx but destination therapy presents itself as a promising option. The increasing demand for LVAD support has lead to the development of different systems with the main difference being their flow characteristics (pulsatile vs. continuous).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Several other studies have concluded that LVAD support is an excellent tool as bridge to transplant [9,10]. As shown by the REMATCH study [3], the role of LVAD support is not only limited as bridge to HTx but destination therapy presents itself as a promising option. The increasing demand for LVAD support has lead to the development of different systems with the main difference being their flow characteristics (pulsatile vs. continuous).…”
Section: Discussionmentioning
confidence: 97%
“…Copeland and associates [2] performed the first bridging to HTx by mechanical support in 1985. Mortality of terminal heart failure being very high as disease progresses, HTx candidates die while waiting on long lists [3,4]. According to the recently published REMATCH study [3], the use of left ventricular assist devices (LVAD) resulted in more than twice the survival rate and an improved quality of life, in comparison to optimal medical management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who were alive on LVAD therapy had significant improvements in HF symptoms (New York Heart Association class II vs IV), mood, exercise capacity, and survival (1-year survival 52% vs 25%; median survival 408 days vs 150 days). 2 The cumbersome pump size and wear and tear of the many interacting components, however, offered opportunity for device failure or pocket infection, ultimately limiting duration of therapy. The leading causes of death for patients randomized to device therapy were sepsis or pump dysfunction, with an expected mechanical pump replacement rate of 63% by 2 years in surviving patients.…”
Section: Pulsatile-flow Devicesmentioning
confidence: 99%
“…The leading causes of death for patients randomized to device therapy were sepsis or pump dysfunction, with an expected mechanical pump replacement rate of 63% by 2 years in surviving patients. 2,3 Continuous-Flow Devices Continuous-flow LVADs, or so-called second-and thirdgeneration LVADs, have been engineered to overcome some of the mechanical limitations of their pulsatile-flow predecessors. Newer-generation LVADs are engineered to minimize the interaction of moving parts, which has significantly prolonged pump durability.…”
Section: Pulsatile-flow Devicesmentioning
confidence: 99%